2011
DOI: 10.3855/jidc.1310
|View full text |Cite
|
Sign up to set email alerts
|

Re-emergence of susceptibility to conventionally used drugs among strains of Salmonella Typhi in central west India

Abstract: Introduction: Typhoid fever (enteric fever) is a global health problem causing high morbidity and mortality, especially in endemic areas such as India. The problem is exacerbated as the causative agent, Salmonella enterica subspecies enterica serovar Typhi (S. Typhi), rapidly develops resistance to drugs used in treatment. However, non-responsiveness of S. Typhi to quinolones has been reported simultaneously with the re-emergence of susceptibility to chloramphenicol. The present study investigates the re-emerg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
18
1
2

Year Published

2011
2011
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 31 publications
(27 citation statements)
references
References 25 publications
(24 reference statements)
4
18
1
2
Order By: Relevance
“…Similarly, a study conducted in eastern Nepal between 2000 and 2004 showed a decreasing trend of MDR Salmonella Typhi [25]. Consistent with our findings, high susceptibility to chloramphenicol, cotrimoxazole, and ampicillin were also reported from different parts of India such as Bangalore, Chennai, Chandigarh, central west, and northern India [3,4,[26][27][28][29]. Re-emergence of chloramphenicol sensitivity was reported in northern India, with 96% sensitivity in Salmonella enterica serovar Typhi and 100% sensitivity in Salmonella enterica serovar Paratyphi A [19].…”
Section: Discussionsupporting
confidence: 79%
“…Similarly, a study conducted in eastern Nepal between 2000 and 2004 showed a decreasing trend of MDR Salmonella Typhi [25]. Consistent with our findings, high susceptibility to chloramphenicol, cotrimoxazole, and ampicillin were also reported from different parts of India such as Bangalore, Chennai, Chandigarh, central west, and northern India [3,4,[26][27][28][29]. Re-emergence of chloramphenicol sensitivity was reported in northern India, with 96% sensitivity in Salmonella enterica serovar Typhi and 100% sensitivity in Salmonella enterica serovar Paratyphi A [19].…”
Section: Discussionsupporting
confidence: 79%
“…High susceptibility to chloramphenicol, cotrimoxazole, and ampicillin were also reported from several parts of India such as Bangaluru, Chennai, Chandigarh, central west, and northern India. 13 A study done by Chand et al 14 revealed reemergence of susceptibility to ampicillin, chloramphenicol and cotrimoxazole in great proportion.…”
mentioning
confidence: 99%
“…19 High susceptibility to chloramphenicol, cotrimoxazole and ampicillin were also reported from several parts of India such as Bangaluru, Chennai, Chandigarh, Central west and northern India. 20 In Bangladesh, study done by Begum et al 13 revealed increased sensitivity to chloramphenicol, ampicillin and cotrimoxazole over the 2 year study periods. Probably, clinicians are not using amoxicillin, cotrimoxazole and chloramphenicol very frequently in this region and drug resistance strains have been eliminated.…”
Section: Discussionmentioning
confidence: 99%